A união estável e a união homoafetiva no direito penal - Toni, Cláudia Thomé (2007)
The modern concept of the rules and principles related to the family reflects the new way of thinking of contemporaneous man, and is the result of the numberless social changes that have occurred throughout history. By way of the exegetical method, we have studied the laws governing the family both in Comparative Law and in the national Law, mainly in the areas of Civil Law and Constitutional Law, and have observed the different kinds of treatment dispensed to different family entities by the Brazilian Criminal Law. The present work has the purpose of suggesting a change in the current provisions of the National Penal Code, so that family entities can be sheltered equally by the Criminal Law, without the current prevalence of marriage as voucher of a stable union. Changes in the Penal Code should be aimed at giving the spouse and the companion the same status, so that any stable union can be recognized as a legitimate family entity by the Criminal Law, and consecrated in all its greatness within our legislative system. Moreover, we shall be dealing with polemic issues derived from the recognition of homosexual unions as family entities, in order to suggest the alteration of articles currently in force in the Penal Code, and to give homoaffective couples the same rights their heterosexual counterparts enjoy. The suggestions are fully justified, since family entities regardless of how they are made up, or of the sex of their members cannot be ignored by the Law, for that does not fit into the reality of our times, and goes against the demands of our society and the provisions of the Federal Constitution of 1988, which provides for ample protection of the family, with no restrictions regarding types (Art. 226, caput, and subsequent §§, Federal Constitution), and which consecrates the dignity of the human person as a fundamental principle of the Federative Republic of Brazil (Art. 1, III, FC). The Criminal Law has to adjust to the new contour just granted to family entities which, today, are characterized by the bonds of love and affection that keep their members together and also to harmonize definitely with what the current constitution dictates, in order to break with formalisms regarding their type of makeup and their characteristics, and thus enhance the protection of this juridical asset of undeniable importance to mankind: the family